2014
DOI: 10.1016/j.nucmedbio.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Al18F-NODA-butyric acid: Biological evaluation of a new PET renal radiotracer

Abstract: Introduction Renal scintigraphy is an important imaging modality for the diagnosis and management of a variety of renal diseases including obstruction and renovascular hypertension as well as the evaluation of absolute and relative kidney function. The goal of this work was to evaluate Al18F-NODA-butyric acid (Al18F-1) as a potential PET tracer to image the kidneys and monitor renal function by comparing its pharmacokinetic properties with those of 131I-o-iodohippurate (131I-OIH), the radioactive standard for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…reported on a robust and straightforward [ 18 F]-labeling route by chelation of Al[ 18 F] with NOTA [31]. Since then, many publications reported the usage of this methodology in labeling peptides, small molecules, and proteins [3235]. Moreover, this methodology has been applied in the clinic in lung cancer patients, by labeling RGD-based peptide, Alfatide [35].…”
Section: Discussionmentioning
confidence: 99%
“…reported on a robust and straightforward [ 18 F]-labeling route by chelation of Al[ 18 F] with NOTA [31]. Since then, many publications reported the usage of this methodology in labeling peptides, small molecules, and proteins [3235]. Moreover, this methodology has been applied in the clinic in lung cancer patients, by labeling RGD-based peptide, Alfatide [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, spatial resolutions of a clinical PET camera and a clinical SPECT camera are 4–6 mm and about 10 mm, respectively. In this regard, we and others have reported a few potential fluorine‐18 ( T 1/2 = 110 min)‐labeled PET renal agents …”
Section: Introductionmentioning
confidence: 93%
“…Although this is a promising methodology for relatively quick labeling of chelator-conjugated molecules, the conditions, such as excessive heating and low pH, may limit the scope of biomolecules that can be labeled by this approach. Since the initial report and subsequent work by the originators, this labeling methodology has been used by several groups for the labeling of small molecules, peptides, and proteins. Wan et al reported recently on the first human study using a new lyophilized kit for the labeling of Al 18 F RGD dimer peptide …”
Section: Radiolabeling Of Biomoleculesmentioning
confidence: 99%